The practices of risk-based internal shariah auditing within Malaysian takaful operators: a multiple case study - Mohamad Puad, Noor Aimi; Shafii, Zurina; Abdullah, Nurdianawati Irwani (Human Resource Management Academic Research Society (www.hrmars.com), 2020)
Shariah audit functions within Islamic Financial Institutions were imposed by Bank Negara Malaysia (BNM) with the issuance of Shariah Governance Framework in 2010. During the early stages of the implementation, the approach for this shariah audit function was only focused on shariah compliance. After ten years, the shariah audit function became mandatory, where this function was expected to be well-developed and able to achieve its primary objective. The role of shariah audit should go beyond Shariah compliance as it should serve as an independent assessment of internal control for any shariah compliance risk. Shariah audit also is one of the crucial elements in the Shariah governance framework. However, the lack of specific guidelines for shariah audit became a challenge for auditors to carry out a comprehensive shariah audit procedure. Therefore, this study aims to provide an in-depth explanation of the process of shariah audit, particularly on planning, executing, reporting and follow up, which emphasises on the application of risk-based internal audit (RBIA) approach. The study adopted a qualitative methodology by using multiple case studies involving Takaful Operators in Malaysia. The detailed explanation of the current shariah audit process is expected to contribute to the provision of valuable detailed information for the Takaful Industry as well as other Islamic financial institutions. The information could benefit Islamic Financial Institutions by assisting in developing a strategy to provide a robust internal control for reducing the occurrence of shariah non-compliance risk.